David Hume and Adam Smith: Similarities and Differences about Sympathy - Altuna, Belén (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
This article presents and contrasts the central role of sympathy in the moral theories of Hume and Smith through five points: 1) the sympathy as the «main source of moral distinctions” and as a counterpoint to selfishness, 2) the auxiliary role of reason, 3) the imaginative mechanism of sympathy, 4) the bias to the partiality that characterizes this mechanism and, therefore, 5) the need for correction recognized by Hume with the «steady and general point of view», and by Smith with the «impartial spectator». Finally, the text reviews the notion of sympathy used by both authors following some contemporary psychological contributions about «empathy», and evaluating the contribution of Smith as the great theorist of the imaginative perspective-taking in all its variants.